Development of Discharge Planning Guidelines for Pediatric Patients with Cancer Receiving Chemotherapy, Maharaj Nakorn Chiang Mai Hospital - Rodaree, Yotsawan; Sonkongdang, Wannita; Arunritthidecha, Asama; Rengrad, Pannee; Wongkom, Sutadta; Sathitsamitphong, Lalita (Nursing Journal CMU, 2022)
Discharge planning is important for the care of pediatric patients with cancer receiving chemotherapy. The purposes of this research were to develop discharge planning guidelines for pediatric patients with cancer receiving chemotherapy at Maharaj Nakorn Chiang Mai Hospital, and to study the feasibility of implementing the guidelines and the satisfaction in using the guidelines for nurses and caregivers of children with cancer receiving chemotherapy. Twelve registered nurses and ten caregivers were selected by purposive sampling. The research was conducted during April to June 2021. The guidelines were developed based on the concept of developing evidence-based practice guidelines of the National Council for Medical and Public Health Research of Australia. The tools for this study were: 1) the guideline development; 2) a guide to caring for pediatric patients with cancer receiving chemotherapy; and 3) an educational multimedia format for infection prevention and control. The validity of the contents was 1. The data was analyzed and expressed as frequency distribution and mean scores. The study results were as follows: there is a possibility of implementing the guidelines in clinical practice. Nurses agreed on the implementation of the guidelines in clinical practice at a moderate to high level with a mean score of 2.89. Caregivers had very good overall satisfaction, with an average score of 4.4. Nurses’ satisfaction scores were at a very good level with an average score of 4.52. The results from this study indicate that the discharge planning guidelines for pediatric patients with cancer receiving chemotherapy at Maharaj Nakorn Chiang Mai hospital, could be implemented and used to conduct research on the effectiveness of discharge planning guidelines.